1998
DOI: 10.1093/emboj/17.14.3858
|View full text |Cite
|
Sign up to set email alerts
|

PED/PEA-15 gene controls glucose transport and is overexpressed in type 2 diabetes mellitus

Abstract: We have used differential display to identify genes whose expression is altered in type 2 diabetes thus contributing to its pathogenesis. One mRNA is overexpressed in fibroblasts from type 2 diabetics compared with non-diabetic individuals, as well as in skeletal muscle and adipose tissues, two major sites of insulin resistance in type 2 diabetes. The levels of the protein encoded by this mRNA are also elevated in type 2 diabetic tissues; thus, we named it PED for phosphoprotein enriched in diabetes. PED cloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
223
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(235 citation statements)
references
References 39 publications
11
223
1
Order By: Relevance
“…The mRNA concentration of PED/PEA15 is increased in fibroblasts, skeletal muscle and adipose tissue of Type II diabetic subjects [45]. In line with this finding, our GeneChip analysis indicated that the PED/PEA15 was expressed marginally higher in the IR versus IS groups.…”
Section: Discussionsupporting
confidence: 80%
“…The mRNA concentration of PED/PEA15 is increased in fibroblasts, skeletal muscle and adipose tissue of Type II diabetic subjects [45]. In line with this finding, our GeneChip analysis indicated that the PED/PEA15 was expressed marginally higher in the IR versus IS groups.…”
Section: Discussionsupporting
confidence: 80%
“…To identify tissues for which PEA15 expression can be noninvasively quantified in a large number of subjects, we first analysed lysates from PBLs by immunoblotting with specific PEA15 antibodies [4]. In samples from 21 subjects (seven with type 2 diabetes, seven euglycaemic subjects with diabetic FDR [EuF+], and seven euglycaemic subjects with no family history of diabetes [EuF−]), these assays revealed the expression of PEA15, with no significant differences between the granulocyte, lymphocyte and monocyte cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins were separated by 15% SDS-PAGE and then transferred to 0.45-mm Immobilon-P membranes (Millipore, Bedford, MA, USA). Filters were probed with phospholipase D1 (PLD1) (BioSource International, Camarillo, CA, USA) or PEA15 antibodies [4], revealed by enhanced chemiluminescence and autoradiography, and PEA15 bands were quantitated by laser densitometry. Inter-assay variation was <15%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations